Analisis dan Perancangan Sistem Informasi Tanggung Jawab Sosial dan Lingkungan dengan pendekatan Scrum - Irfanda Wira Arnawama (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Corporate social responsibility (CSR) is a form of policy or activity organized by an organization or business entity in contributing to the community and the environment. In Indonesia, social responsibility is carried out in the Social and Environmental Responsibility which called TJSL program. The main problem in implementing CSR is in data management and reporting. This can be caused by manual data management in excel files. the use of Microsoft Excel in processing transaction data is very error-prone because the data is entered manually and can cause a chain effect in data collection. To overcome this problem, it is necessary to develop a TJSL program management application which will be developed using an agile approach with the scrum method. The test method on the SR APP module of the TJSL uses the black-box testing method and the user acceptance test. The results of the load testing explained that the system can be accessed by up to 245 users at the same time and the user acceptance test obtained a value of 89.8% which explains that the application is good and accepted by users.